(untitled) (Sport - nauka i praksa, 2023)
The primary aim of the paper is to conduct research on the personality traits in esport players and athletes, in addition to confirming differences in personality between the two examined groups. The research has been conducted on 67 (N=67) examinees, 30 of whom are semi-professional or professional esports players who participate in state-level and regional-level competitions. The remaining 37 examinees are the highest-ranked athletes in Bosnia and Herzegovina. T-test, a type of inferential statistic, has been used to determine statistical differences in disposition between the arithmetic means of the two groups, using the BFI-44 (α=0.78) measuring instrument. It has been anticipated that esports players would be ranked lower on Extraversion (E), Agreeableness (A), and Conscientiousness (C), but higher on the Neuroticism (N) and Openness (O) dimensions compared to athletes. The research indicates that four of the five hypotheses have been confirmed – on the scale of Extraversion (E) with significance levels of p=.000 (p<0.0001); Agreeableness (A) showing p=.002 (p<0.01); Neuroticism (N) showing p=.042 (p<0.05); and Conscientiousness (C) showing significance levels of p=.004 (p<0.01) The fifth hypothesis was not confirmed on this sample. The results gathered on this sample could significantly contribute to understanding the differences between esports players and athletes.